Corporate tax aggression and debt in Iran - Salehi, Mahdi; Salami, Shantia (Journal of Islamic accounting and business research, 2020)
Purpose This study aims to investigate the impact tax shelters and cost of debt in Iran. It also aims determine methods to identify tax-aggressive policies through corporate structure and corporate policies, as well as various solutions to handle these issues. Design/methodology/approach For this purpose, the data of 155 listed companies on the Tehran Stock Exchange (TSE) during the years of 2008-2015 will be considered. The number of observations includes 1,085 companies. Data was analyzed using logistic panel regression with R software. Findings The results of the hypotheses show that financial leverage use is not inversely related to companies’ tax-aggressive policies. There is no direct relationship between sales and financial leverage. Overall, there is no inverse relationship between tax shelters and total debt. Originality/value The results extend the empirical findings of Graham and Tucker and Wilson. The authors also investigated the relationship between tax shelters and financing (total debt). These findings are crucial to the state; although several studies with similar subjects have been conducted in different countries, the current study is the first of its type in Iran.